Effect of frictions on cross section quality of thin-walled tube NC bending - 杨合 谷瑞杰 詹梅 李恒 (Transactions of Nonferrous Metals Society of China, 2006)
The effect of frictions between dies and tube on the cross section quality of thin-walled tube numerical controlled（NC） bending was studied by numerical simulation method, combined with theoretical analysis and experiment. The results show that the frictions between mandrel, wiper, pressure die, bending die and tube have a significant and complicate effect on the section quality of thin-walled tube NC bending. To improve the section quality, frictions between mandrel, wiper and tube should be decreased, but the frictions between the pressure die, bending die and tube increase. The effect on the section distortion is more significant from mandrel, wiper, pressure die to bending die and the effect on the wall thinning more significant from mandrel, pressure die, wiper, to bending die. The effects of frictions between all dies and tube on wall thinning are smaller than their effects on section distortion. Mandrel and wiper should be lubricated well and drawing oil is used to lubricate them in actual production. The frictions between pressure die, bending die and tube should be increased and the dry friction is used between pressure die, bending die and tube in actual production.